Drought risk reduction in agriculture: A review of adaptive strategies in East Africa and the Indo-Gangetic plain of South Asia - Cenacchi, Nicola (International Food Policy Research Institute, 2014)
This report is a component of the Research Program on Climate Change, Agriculture, and Food Security (CCAFS)–-funded project “Impacts of Climate Extremes on Future Water and Food Security in South Asia and East Africa.” The goal of the project was to characterize extreme drought events, to improve on a methodology to assess the probability of these events in the future under climate change, to illustrate their impacts, and to provide suggestions on coping strategies. The present report sets the stage for the overall project by undertaking a review of the causes of vulnerability to drought in East Africa and the western Indo-Gangetic Plain (IGP) of South Asia, and discussing the options to increase resilience to drought in the agricultural sector. Agriculture is a high-risk endeavor in both regions, due to a combination of recurrent droughts—which may intensify due to climate change—poor soil fertility, and a host of constraints faced by farmers, especially low access to input and output markets. These factors, combined with farmers’ high aversion to risk, stifle investments in agriculture, resulting in continuous underachieving production, low income, and persisting poverty.